2011
DOI: 10.1590/s0100-40422011000600007
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and robust lc-ms/ms method with monolithic column and electrospray ionization for the quantitation of efavirenz in human plasma: application to a bioequivalence study

Abstract: Recebido em 12/7/10; aceito em 17/12/10; publicado na web em 25/3/11An LC-MS/MS method has been developed for the determination of efavirenz (EFZ) in human plasma using hydrochlorothiazide as internal standard (I.S.). An ESI negative mode with multiple reaction-monitoring was used monitoring the transitions m/z 313.88→69.24 (EFZ) and 296.02→204.76 (I.S.). Samples were extracted using liquid-liquid extraction. The total run time was 2.0 min. The separation was achieved with HPLC-RP using a monolithic column. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…The reference drug product (Stocrin Ò , 600 mg tablets) was commercially available at the time of the study. Details of clinical data from the approved biobatch can be found in Honorio et al [10], and for the not approved biobatch in Bedor et al [9]. Prior to volunteer recruitment, all protocols were approved by the research ethics committee, as detailed in each specific study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference drug product (Stocrin Ò , 600 mg tablets) was commercially available at the time of the study. Details of clinical data from the approved biobatch can be found in Honorio et al [10], and for the not approved biobatch in Bedor et al [9]. Prior to volunteer recruitment, all protocols were approved by the research ethics committee, as detailed in each specific study.…”
Section: Methodsmentioning
confidence: 99%
“…The bioequivalence studies were conducted on volunteers whose age ranged between 18 and 45 years. The analytical tests and details of these studies were reported by Bedor et al [9] and Honorio et al [10], who followed the Brazilian protocol for bioequivalence studies [11], in accordance also with international recommendations for this kind of evaluation. Apart from the in vivo studies, so far there are no clear explanations for the dissolution (in vitro) tests with the specific conditions used in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The average analysis time was 8 min. The plasma concentration of EFV was determined using HPLC coupled to a mass detector (LC-MS/ MS 3200 QTRAP from Sciex V R , Toronto, Canada), following a previously described protocol [28]. An isocratic elution mode of the analytes from an Onix C18 monolithic column (L: 50 mm; i.d: 4.6 mm) (Phenomenex V R , Torrance, USA) was achieved with a mobile phase consisting of acetonitrile/water (50:50 v/v þ 5% isopropyl alcohol, v/v).…”
Section: Sample Analysesmentioning
confidence: 99%
“…Проведенный анализ литературы и нормативных документов по контролю качества эфавиренза [4,7,9,10] показал, что рекомендованным методом количественного определения исследуемого лекарственного средства является метод высокоэффективной жидкостной хроматографии.…”
unclassified